2019
DOI: 10.3390/a12060121
|View full text |Cite
|
Sign up to set email alerts
|

Learning Output Reference Model Tracking for Higher-Order Nonlinear Systems with Unknown Dynamics

Abstract: This work suggests a solution for the output reference model (ORM) tracking control problem, based on approximate dynamic programming. General nonlinear systems are included in a control system (CS) and subjected to state feedback. By linear ORM selection, indirect CS feedback linearization is obtained, leading to favorable linear behavior of the CS. The Value Iteration (VI) algorithm ensures model-free nonlinear state feedback controller learning, without relying on the process dynamics. From linear to nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Proof. By Lemma 1, we know that the Q-function (27) in input-output form is equivalent to the original Q-function (14). Due to the excitation noise, the actual control input to collect data isû k = u k + w k with w k being the probing noise signals.…”
Section: End Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. By Lemma 1, we know that the Q-function (27) in input-output form is equivalent to the original Q-function (14). Due to the excitation noise, the actual control input to collect data isû k = u k + w k with w k being the probing noise signals.…”
Section: End Proceduresmentioning
confidence: 99%
“…Most of the existing studies rely on the available measurement of full state information, see [22], [27] and the references therein. However, it may not be feasible in practical implementations [28], and therefore, it is desirable to design output feedback (OPFB) learning controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining an optimal policy in reasonable time, taking decisions and actions under large state-spaces using DRL have been applied to network access, wireless caching, cognitive spectrum sensing, and network security. Some of the more recent DRL applications include modeling multiple experience pools for UAV autonomous motion planning in complex unknown environments [ 9 ], learning output reference model tracking for higher-order nonlinear systems with unknown dynamics [ 10 ], and pick and place operations in logistics using a mobile manipulator controlled with DRL [ 11 ]. The DRL paradigm has been extended to domains such as autonomous vehicles and has opened new research avenues [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Responding to the needs, there have been various studies and algorithms developed for autonomous flight systems. Especially, many ML-based (Machine-learning based) methods have been proposed for autonomous path finding [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, they are limited when applied to a large target area.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Radac and Lala [ 23 ] showed that VIN algorithm’s convergence is guaranteed under general function approximators with providing a case study for a low-order linear system in order to generalize the more complex ORM tracking validation on a real-world nonlinear multi-variable aerodynamic process. Considering these advantages of VIN over DQN- or DDPG-based algorithms, we choose a VIN method as a baseline path planning algorithm.…”
Section: Introductionmentioning
confidence: 99%